SEAWEED AS A DIETARY FIBER TO PREVENT THE CARDIOVASCULAR DISEASE - Andri Nofreeana; Muh. Azril (Journal of Aquaculture Development and Environment, 2022)
Indonesia has a lot of potential in natural resources, one of which is seaweed. Seaweed is one of the natural ingredients that contain water-soluble dietary fiber. The fiber content in seaweed can be categorized as a functional food. The fiber content in seaweed varies, from 36-60% dry weight, 55-70% of the former percentage is soluble fiber consisting of alginate and carrageenan with varying amounts depending on the type of seaweed and environmental conditions. The dietary fibers are useful for disease prevention and health maintenance. Dietary fiber can prevent several diseases, including coronary heart disease (cardiovascular). The effect of dietary fiber according to Liu et al (2002) is a very high fiber diet (55 g/1,000 kcal) which resulted in a 33% reduction in LDL cholesterol (Low-Density Lipoprotein) in two weeks period. The mechanism of dietary fiber reduces cardiovascular disease since it is able to bind bile acids (the end product of cholesterol), thereby preventing its reabsorption from the intestine. Cholesterol that is bound to bile acids and lignin/pectin cannot be absorbed by the intestines but will be excreted in the feces.